Experimental study of shale drillability with different bedding inclinations under varying wellbore pressure conditions - Shuai Chen; Xiangchao Shi; Heng Bao; Leiyu Gao; Jie Wu (Journal of Petroleum Exploration and Production Technology, 2021)
Abstract In the practice of shale gas development engineering, it is important to understand the physical and mechanical properties of shale. The bedding inclinations of shale are known to significantly influence its physical and mechanical properties. This study mainly examined the influence of bedding inclinations on drillability under different wellbore pressures. The bedding inclinations used in this study varied from 0° to 90°, with a gradient of 15°. The wellbore pressure values used varied from 0 to 25 MPa, with a gradient of 5 MPa. The results show that the drillability index of shale increases exponentially with increasing wellbore pressure at different bedding inclinations. The proposed exponential empirical model can describe the relationship between the drillability index and wellbore pressure. When the wellbore pressure is less than 15 MPa, bedding inclinations significantly influence the drillability index, and the drillability index of shale shows a “W”-type variation trend as the bedding inclinations increase in the range of 0° to 90°. The influence of bedding inclinations on drillability decreases gradually with increasing wellbore pressure. When the wellbore pressure increases to 25 MPa, the impact of bedding inclinations on drillability is virtually undetectable. The results of this study can provide reasonably insight into the effect of bedding inclinations on shale deformation under the drill bit, and useful prediction for the drillability index under in situ conditions.